SANITASI DAN BIOSEKURITI YANG EFEKTIF PADA TERNAK - Noywuli, Nicolaus; Ngaku, Maria Alfonsa; Bii Bei, Maria Imelda; Nono, Louis M.D. Pati; Pawe, Maria.E.; Lay, Mario Alesandro; Sua, Yoris Pitika (Agros Journal of Agriculture Science, 2024)
Animal husbandry is an effort to cultivate livestock which is used to produce milk, meat and eggs. In animal husbandry, pest and disease control is required, so in animal husbandry we look for ways to ensure that livestock are free from disease outbreaks. The aim of this study is to find out how effective sanitation and biosecurity methods are used. is a literature study or literature study. The results of this paper show that sanitation is an action to kill bacteria, while biosecurity is all actions for the first defense in controlling an outbreak which is carried out by preventing all possibilities of transmission with infected livestock so that the chain of spread can be minimized. The three components of biosecurity measures are Isolation, traffic control, prusip sanitation, effective sanitation and biosecurity are preparation and prevention for early detection, identification of biological and chemical agents, bioterrorism response.